PENINGKATAN KECERDASAN KINESTETIK MELALUI KEGIATAN BERMAIN SIRKUIT DENGAN BOLA (Penelitian Tindakan di Kelompok A TK Al Muhajirin Malang Jawa Timur, Tahun 2015) - Denok Dwi Anggraini (Universitas Trunojoyo Madura, 2015)
Increase Kinesthetic Intelligence Through Play Activities Circuit With Ball. The purpose of this research was to determine the process of implementation of the circuit with a ball playing in increasing child kinesthetic intelligence in group A in Al Muhajirin Kindegarten Malang and to know the extent to which the results of the increase in child kinesthetic intelligence through a circuit with a ball playing in group A Al Muhajirin Kindegarten Malang.The method used in this research is an action research which refers to the model of a Classroom Action Research Kemmis and Mc. Taggart consist of four phase: planning, action, observation and reflection. This research consist of two cycles, each cycle consist of 8 times in actions. Analysis of the data used quantitative and qualitative approaches. The results showed an increase kinesthetic intelligence through circuits with a ball playing activities, it can be proven scoring average pre-action children's kinesthetic intelligence by 32.81%. And then increased in the first cycle by 37.44% to become 70.25%. Furthermore, from the first cycle to the second cycle kinesthetic intelligence of children increased by 17.91% from 70.25% to 88.16%. So the total increase kinesthetic intelligence of children ranging from pre-action, the first cycle to the second cycle is 32.81% 70.25% to 88.16%.